Modified New Microporous Carbon Layer Structure for Improved PEM Fuel Cell Performance with Low-Pt Catalyst Loadings. Issue 10 (21st October 2021) - Daniel, Lius; Bonakdarpour, Arman; Govindarajan, Rubenthran; Wilkinson, David P.
Abstract : Three types of commercial carbon black with different porosity and hydrophilicity were investigated at various conditions in a new architecture of microporous carbon layers where they are deposited directly on the low loading cathode catalyst layers (0.1 mgPt cm −2 ) of membrane electrode assemblies (MEAs) used in H2 /O2 fuel cells. The benefits of this modified microporous layer (MPL) include reduced interfacial gaps present between the catalyst layer and the conventional MPL-coated gas diffusion layer of the MEAs, reduced water accumulation, and therefore, higher power densities. Acetylene Black and Vulcan XC72R based modified MPLs with mass loadings in the range of 0–1.0 mg cm −2 show improved fuel cell performance in the higher current density regions due to their lower porosity and higher hydrophobicity. The MPL optimum loading under wet and dry conditions is found to be around 0.8 mg cm −2 (∼20 μ m), at which a power gain of up to ∼37% is possible as a result of the improved interlayer contact and mass transport under wet conditions as well as enhanced membrane and cathode catalyst layer hydration under dry conditions. Detailed performance characteristics and longer-term studies performed under different humidification levels were also examined and are discussed in this paper.